2012
DOI: 10.1098/rsbl.2011.1234
|View full text |Cite
|
Sign up to set email alerts
|

An invasive species reverses the roles in a host–parasite relationship between bitterling fish and unionid mussels

Abstract: The impact of multiple invading species can be magnified owing to mutual facilitation—termed ‘invasional meltdown’—but invasive species can also be adversely affected by their interactions with other invaders. Using a unique reciprocal host–parasite relationship between a bitterling fish ( Rhodeus amarus ) and unionid mussels, we show that an invasive mussel reverses the roles in the relationship. Bitterling lay their eggs into mussel gills, and mussel larvae parasitize fish. Bitterling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…While populations from Central Poland were used by R. amarus for oviposition, with all bitterling embryos later ejected, S. woodiana populations from the southern Czech Republic were completely avoided by R. amarus , thereby mitigating the costs of failed development. Hence, the identity of S. woodiana populations determines the impact of S. woodiana on native R. amarus , from almost neutral to highly negative (Reichard, Vrtílek, Douda, & Smith, ; Reichard et al., ). The current study demonstrated that the two S. woodiana populations previously used to test their response to bitterling fish are genetically differentiated (PLLI and CZKY populations, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…While populations from Central Poland were used by R. amarus for oviposition, with all bitterling embryos later ejected, S. woodiana populations from the southern Czech Republic were completely avoided by R. amarus , thereby mitigating the costs of failed development. Hence, the identity of S. woodiana populations determines the impact of S. woodiana on native R. amarus , from almost neutral to highly negative (Reichard, Vrtílek, Douda, & Smith, ; Reichard et al., ). The current study demonstrated that the two S. woodiana populations previously used to test their response to bitterling fish are genetically differentiated (PLLI and CZKY populations, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Bivalve molluscs are ubiquitous, sedentary filter feeders, which can bio-accumulate pollutants to a high degree [16,17]. The Chinese pond mussel (the Eastern Asiatic freshwater clam or swanmussel), bivalve Anodonta woodiana functions as a main criteria required for a bio-indicator organism [18,19]. Earlier studies have revealed the ability of Sinanodonta woodiana to accumulate trace elements and pesticides [20,21], as well as its potential to detect genotoxicity [22].…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization occurs in the mussel gill cavity and development is completed in the host mussel gill chamber (Smith et al, 2004). This breeding association makes species of bitterlings a focus of research aimed at understanding coevolutionary dynamics, life-history evolution, sexual selection, sperm competition, development and mate choice (Agbali et al, 2011;Casalini et al, 2009;Kitamura et al, 2012;Mills et al, 2005;Reichard et al, 2006Reichard et al, , 2007Reichard et al, , 2012; .…”
Section: Introductionmentioning
confidence: 99%